Volatile fatty acids production from biowaste at mechanical-biological treatment plants: Focusing on fermentation temperature. (October 2020) - Fernández-Domínguez, David; Astals, Sergi; Peces, Miriam; Frison, Nicola; Bolzonella, David; Mata-Alvarez, Joan; Dosta, Joan
Highlights: Weak impact of fermentation temperature (20–70 °C) on VFA yield and VFA profile. Biowaste fermentation at 35 °C showed VFA yields ranging 0.49–0.59 g CODVFA /g VS. Differences on VFA yield for tests carried out between 20 and 55 °C were below 10%. VFA profile was not affected by temperature and was dominated by HAc, HPro and HBu. The integration of a fermentation unit in the MBT plant is conceived and discussed. Abstract: The impact of temperature (20, 35, 45, 55, 70 °C) on volatile fatty acid (VFA) production from biowaste collected at a mechanical–biological treatment plant was analysed. Additionally, relevant streams of the treatment plant were characterised to assess seasonality effects and conceive the integration of a fermentation unit. Batch fermentation tests at 35 °C showed the highest VFA yields (0.49–0.59 gCODVFA /gVS). The VFA yield at 35 °C was 2%, 6%, 10% and 14% higher than at 55, 45, 20 and 70 °C, respectively. The VFA profile was not affected by the fermentation temperature nor seasonality and was dominated by acetic, propionic and butyric acid (75–86% CODVFA ). The concentration of non-VFA soluble COD and ammoniacal nitrogen in the fermentation liquor increased with temperature. The fermentation unit in the treatment plant was conceived after the pulper and hydrocyclones and before the anaerobic digester, while the fermenter temperature depends on the VFA application.